Mitochondrial DNA induces inflammation and increases TLR9/NF-κB expression in lung tissue - Zhang, Jian-Zheng; Liu, Zhi; Liu, Jia; Ren, Ji-Xin; Sun, Tian-Sheng (International journal of molecular medicine, 2023)
Following the publication of this paper, it was drawn to the Editor's attention by a concerned reader that several of the western blotting images shown in Fig. 4 on p. 822 were strikingly similar to data which had appeared in Fig. 5A of the following paper: Fan J, Frey RS and Malik AB: TLR4 signaling induces TLR2 expression in endothelial cells via neutrophil NADPH oxidase. J Clin Invest 112: 1235‑1243, 2003. Owing to the fact that the contentious data in the above article had already been published elsewhere prior to its submission to , the Editor has decided that this paper should be retracted from the Journal. The authors were asked for an explanation to account for these concerns, but the Editorial Office did not receive a reply. The Editor apologizes to the readership for any inconvenience caused. [International Journal of Molecular Medicine 33: 817‑824, 2014; DOI: 10.3892/ijmm.2014.1650].